A coating material for coated aluminum plate and preparation method thereof
By adding modified functional resin and modified particles to the coating material for coated aluminum plates, a three-dimensional three-dimensional connection network structure and an electronically-unicom composite structure is formed, which solves the problem that existing coating materials are difficult to take into account multiple properties, significantly improves the waterproof, anti-static and aging resistance of the coating material, and extends the service life of the coated aluminum plates.
Patent Information
- Application Number
- CN202411060636.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing surface coating materials for coated aluminum plates are difficult to take into account both waterproofness, antistatic properties, weathering and light resistance, and paint dropping, cracking and bubbles are prone to occur during long-term use, which affects the quality and life of coated aluminum plates.
The coating material is adopted with aqueous polyurethane emulsion as the main material, and modified functional resin and modified particles are added to form a three-dimensional three-dimensional connection network structure and an electronic communication composite structure to enhance the waterproof, anti-static and aging resistance of the coating material.
It significantly improves the waterproofness, antistatic properties, weathering and light resistance of the coating material, avoids paint loss, cracking and bubble formation, extends the service life of the coated aluminum plate, and takes into account the adhesive properties.
Smart Images

Figure BDA0004977753450000161 
Figure BDA0004977753450000171
Abstract
Description
Technical Field
[0001] The present application relates to the field of coatings, and in particular to a coating material for a laminated aluminum plate and a preparation method thereof. Background Art
[0002] Laminated aluminum sheet is a composite material made by bonding plastic film or other types of films to the surface of aluminum sheet. This material combines the high strength and light weight of aluminum sheet with the decorative and protective properties of film, and is widely used in architectural decoration, home appliance manufacturing, advertising signs and other fields.
[0003] In recent years, with the continuous increase in the application fields and environmental scenarios of coated aluminum sheets, the application of surface coating materials for coated aluminum sheets has also increased. They are often coated on the surface of the film in some specific environments and fields to provide more surface properties of the aluminum sheet. And as people's diversified needs for coated aluminum sheets increase, the functional requirements for their surface coating materials are also gradually increasing.
[0004] However, there are still some technical difficulties in the existing surface coating materials for laminated aluminum sheets. For example, in some specific application environments, there are high requirements for the waterproofness, antistatic properties, weathering resistance and light resistance of laminated aluminum sheets and their surface coatings. However, few surface coating materials for laminated aluminum sheets can effectively meet the above multiple requirements at the same time, and in order to improve the above performance, some surface coating materials have given up some surface adhesion properties, which leads to paint peeling, cracking and blistering during the long-term use of laminated aluminum sheets, which greatly affects the quality and life of the laminated aluminum sheets.
[0005] Therefore, in order to solve the above-mentioned problems, the present application provides a coating material for laminated aluminum plates and a preparation method thereof. The coating material for laminated aluminum plates prepared in the present application uses polyurethane as the main material to ensure its adhesion to the laminated aluminum plates, and on this basis, greatly enhances the waterproofness, antistatic properties, weather resistance, light resistance and other properties of the coating material during long-term use. Unlike the existing surface coating materials for laminated aluminum plates, it can take into account and balance multiple surface properties, thereby enhancing the application effect of the laminated aluminum plates, avoiding the technical problems of existing coating materials for laminated aluminum plates, and has very excellent market and application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a coating material for a laminated aluminum plate. The raw materials are, by mass: 75 to 95 parts of aqueous polyurethane emulsion, 25 to 40 parts of modified functional resin, 20 to 30 parts of modified particles, 5 to 15 parts of additives, 6 to 12 parts of dispersants, 2 to 5 parts of adhesion promoters, 5 to 8 parts of curing agents, 1.5 to 3 parts of leveling agents, 0.5 to 1.5 parts of defoaming agents, and 140 to 200 parts of deionized water.
[0007] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, the modified functional resin and the auxiliary agent is (8-9): (2.5-3.5): (0.6-1.4).
[0008] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, the modified functional resin and the auxiliary agent is (8-8.5): (2.5-3): (0.8-1.2).
[0009] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, the modified particles and the dispersant is (8-9): (2.2-2.8): (0.8-1.2).
[0010] As a preferred solution, the mass ratio of the aqueous polyurethane emulsion, the modified particles and the dispersant is (8-8.5): (2.4-2.6): (0.8-1).
[0011] As a preferred solution, the aqueous polyurethane emulsion is an anionic aqueous polyurethane emulsion.
[0012] As a preferred solution, the solid content of the aqueous polyurethane emulsion is 40-50%.
[0013] As a preferred solution, the viscosity of the aqueous polyurethane emulsion is 300-500 mPa·s, and the test condition is 25°C.
[0014] As a preferred solution, the viscosity of the aqueous polyurethane emulsion is 400-450 mPa·s, and the test condition is 25°C.
[0015] As a preferred solution, the preparation method of the modified functional resin comprises the following steps: S1: adding ethylene glycol diacrylate, mercaptoethyl acrylate and acrylonitrile to an organic solvent, introducing nitrogen, adding an initiator, heating to 70-90°C for reaction for 4-5 hours to obtain a pre-product solution; S2: adding acrylamide, dodecyl acrylate, deionized water and an initiator to the pre-product solution obtained in S1, and heating to 80-90°C for reaction for 4-8 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding an alkali agent to adjust the pH to 7-7.5, and after completion, filtering and washing the product to obtain the product.
[0016] As a preferred solution, the mass ratio of ethylene glycol diacrylate, mercaptoethyl acrylate and acrylonitrile is (4-6): (2-3): (8-12).
[0017] As a preferred solution, the mass ratio of acrylonitrile, acrylamide and dodecyl acrylate is (8-12):(30-40):(5-6).
[0018] As a preferred solution, the initiator is ammonium persulfate or potassium persulfate.
[0019] As a preferred solution, the alkali agent is diethanolamine, triethanolamine, ammonia water, and the modified functional resin added in this application can greatly improve the waterproofness, antistatic and aging resistance of the coating material. The modified functional resin added in this application can first form a three-dimensional and stable three-dimensional connection network structure in the coating material system through the entanglement and connection of its long chain, and the existence of the network structure can establish a good intermolecular force with the added modified particles through its molecular chain, and increase the steric hindrance between active molecules through the joint action of pore action and intermolecular force, thereby greatly reducing and changing the reaction path in the aging reaction, and greatly reducing the collision probability between active molecules and water molecules, thereby greatly improving the aging reaction resistance, and effectively reducing the distance between water molecules in the coating, and reducing the formation speed of the hydration permeation layer of the surface layer, thereby obtaining excellent aging resistance and waterproof performance.
[0020] On the other hand, the added modified functional resin can enhance the extension effect of the modified particles in the coating material through the guiding effect of its long molecular chain, thereby forming a surface with a higher content of modified particles and a rougher surface on the coating surface. The rough surface can greatly reduce the formation speed of the hydration layer on the coating surface by virtue of the extremely low surface energy and peak-to-valley structure of the modified particles, thereby enhancing the surface water resistance and greatly limiting the infiltration of water molecules; and the presence of the modified functional resin helps the dispersion of the modified particles to fully exert their role as electron pathways, thereby maintaining a good charge transfer effect during long-term use, and thus having excellent antistatic properties.
[0021] As a preferred solution, the preparation method of the modified particles comprises the following steps: S1: adding carbon black and zinc oxide to a DMF solution, adding succinic anhydride and a silane coupling agent and heating to 65-75°C, stirring for reaction for 2-3h, cooling naturally to room temperature after the reaction is completed, and washing and filtering the product to obtain mixed particles; S2: adding the mixed particles back to the DMF solution, adding succinic anhydride and a silane coupling agent for a second time, and simultaneously adding trimesic acid and an aqueous solution containing copper nitrate for ultrasonic dispersion for 10-15min to obtain a mixed solution; S3: adding the mixed solution to a high-pressure reactor and heating to 90-110°C to keep the temperature for reaction for 10-15h; S3: after the reaction is completed, adding triethanolamine, mixing and stirring for 0.5-1h, adjusting the pH to 7-7.5 to obtain the final product, centrifuging and filtering the final product, washing with methanol and vacuum drying at 80-90°C for multiple cycles, and obtaining the final product after completion.
[0022] As a preferred solution, in S1, the mass ratio of carbon black, zinc oxide, succinic anhydride and silane coupling agent is (3-4): (1.1-1.2): (1.4-1.8): (0.4-0.5).
[0023] As a preferred solution, the average particle size of the carbon black is 40 to 60 nm.
[0024] As a preferred solution, the average particle size of the zinc oxide is 10 to 25 nm.
[0025] As a preferred solution, in S2, the mass ratio of the mixed particles, succinic anhydride, and silane coupling agent is (2-2.5): (1.2-1.4): (0.2-0.3).
[0026] As a preferred solution, the mass ratio of trimesic acid to copper nitrate in the mixed particles is (2-2.5):(0.4-0.6):(1.1-1.5).
[0027] As a preferred solution, the silane coupling agent is at least one of 3-aminopropyltriethoxysilane, vinyltriethoxysilane, and γ-aminopropyltrimethoxysilane.
[0028] As a preferred solution, the average particle size of the modified particles is 600-750 nm.
[0029] The modified particles added in the present application can greatly improve the waterproof, antistatic, aging and light resistance of the coating material. The modified particles added in the present application can form a good electronic interconnection composite structure through the coordination combination of the composite particles. The existence of this structure not only greatly increases the length of the electron flow path, but also promotes the aggregation of electrons and holes on the particle surface, thereby greatly enhancing the light energy absorption effect of the modified particles, and having good light resistance; on the other hand, the formed composite structure can ensure that the structure of the framework particles in the center is exposed to the surface by controlling the particle size, thereby giving the composite modified particles excellent hydrophobic properties through their extremely low surface energy, and greatly reducing the content of water molecules inside the coating material, thereby maintaining excellent waterproof and weather resistance during long-term use.
[0030] As a preferred solution, the auxiliary agent at least includes a thickener and a mildew preventer.
[0031] As a preferred solution, the mass ratio of the thickener to the mildew inhibitor is (5-10): (0.5-1.5).
[0032] As a preferred solution, the thickener is at least one of hydroxyethyl cellulose, methyl cellulose, hydroxypropyl cellulose, sodium carboxymethyl cellulose and polyvinyl alcohol.
[0033] As a preferred solution, the thickener is a combination of hydroxyethyl cellulose and polyvinyl alcohol.
[0034] As a preferred solution, the mass ratio of hydroxyethyl cellulose to polyvinyl alcohol is (4-6): (1-2).
[0035] As a preferred solution, the dispersant is at least one of sodium polycarboxylate, ammonium polycarboxylate, polyethylene glycol ether, lauryl alcohol polyoxyethylene ether, cetyl alcohol polyoxyethylene ether, sodium dodecylbenzene sulfonate, and polyethylene glycol.
[0036] As a preferred solution, the dispersant is cetyl alcohol polyoxyethylene ether.
[0037] As a preferred solution, the hydroxyl value of the cetyl alcohol polyoxyethylene ether is 80 to 150 mgKOH / g.
[0038] As a preferred solution, the hydroxyl value of the cetyl alcohol polyoxyethylene ether is 90 to 120 mgKOH / g.
[0039] As a preferred solution, the adhesion promoter is at least one of chlorinated polypropylene, γ-aminopropyltriethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.
[0040] As a preferred solution, the adhesion promoter is a composition of γ-aminopropyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0041] As a preferred solution, the mass ratio of γ-aminopropyltriethoxysilane to γ-glycidyloxypropyltrimethoxysilane is (2-2.5):(1-1.2).
[0042] As a preferred solution, the curing agent is at least one of polyisocyanates, ethylenediamine, and cyclohexanediamine.
[0043] As a preferred solution, the curing agent is polyisocyanate.
[0044] As a preferred solution, the polyisocyanate is any one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and naphthalene diisocyanate.
[0045] As a preferred solution, the leveling agent is at least one of an organic silicone leveling agent, an acrylate copolymer leveling agent, a polyethylene wax, and a polytetrafluoroethylene wax.
[0046] As a preferred solution, the leveling agent is polyethylene wax.
[0047] As a preferred solution, the defoaming agent is at least one of silicone defoaming agents.
[0048] The second aspect of the present application provides a method for preparing the coating material for the above-mentioned coated aluminum plate, which specifically includes the following steps: first, the modified particles and the modified functional resin are evenly mixed and then added to a high-speed mixer together, and then the aqueous polyurethane emulsion, deionized water and the remaining raw materials are added in sequence, the temperature is raised to 40-50°C, and the high-speed mixing is carried out at a speed of 300-450rpm for 30-45min. Finally, the mixed material is ground and dispersed in a grinder for 4-6h. After completion, it is naturally cooled to room temperature, and the product is left to stand for 2-4h.
[0049] The beneficial effects of this application are:
[0050] 1. The coating material for laminated aluminum plates provided in the present application uses polyurethane as the main material to ensure its adhesion to the laminated aluminum plates, and on this basis, greatly enhances the waterproofness, antistatic properties, weather resistance, light resistance and other properties of the coating material during long-term use. Different from the existing surface coating materials for laminated aluminum plates, it can take into account and balance multiple surface properties, thereby enhancing the application effect of the laminated aluminum plates, avoiding the technical problems of the existing coating materials for laminated aluminum plates, and has very excellent market and application prospects.
[0051] 2. A coating material for a laminated aluminum plate provided in the present application can greatly improve the water resistance, antistatic properties and aging resistance of the coating material by adding a modified functional resin; the added modified functional resin can firstly form a three-dimensional and stable three-dimensional connected network structure in the coating material system through the entanglement and connection of its long chains, and the existence of the network structure can establish a good intermolecular force with the added modified particles through its molecular chain, and increase the steric hindrance between active molecules through the joint action of pore action and intermolecular force, thereby greatly reducing and changing the reaction path in the aging reaction, and greatly reducing the probability of collision between active molecules and water molecules, thereby greatly improving the aging reaction resistance.
[0052] 3. A coating material for a coated aluminum plate provided in the present application, the added modified functional resin can enhance the ductility effect of the modified particles in the coating material through the guiding effect of its long molecular chain, thereby forming a surface with a higher content of modified particles and a rougher surface on the coating surface. The rough surface can greatly reduce the formation speed of the hydration layer on the coating surface by virtue of the extremely low surface energy and peak-to-valley structure of the modified particles, thereby enhancing the surface water resistance and greatly limiting the infiltration of water molecules; and the presence of the modified functional resin helps the dispersion of the modified particles to fully exert their role as electron pathways, thereby maintaining a good charge transfer effect during long-term use, thereby having excellent antistatic properties.
[0053] 4. A coating material for a coated aluminum plate provided in the present application, the added modified particles can greatly improve the waterproof, antistatic, aging resistance and light resistance of the coating material; the added modified particles can form a good electronic interconnection composite structure through the coordination combination of composite particles, the existence of this structure not only greatly enhances the length of the electron flow path, but also promotes the aggregation of electrons and holes on the surface of the particles, thereby greatly enhancing the light energy absorption effect of the modified particles, and having good light resistance; on the other hand, the formed composite structure can ensure that the structure of the framework particles in the center is exposed to the surface by controlling the particle size, and then endow the composite modified particles with excellent hydrophobic properties through their extremely low surface energy, and greatly reduce the content of water molecules inside the coating material, thereby maintaining excellent waterproof and weather resistance during long-term use. DETAILED DESCRIPTION
[0054] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0055] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0056] Example 1
[0057] Example 1 The first aspect provides a coating material for a laminated aluminum plate. The raw materials are, in parts by mass: 84.5 parts of aqueous polyurethane emulsion, 26.8 parts of modified functional resin, 24.5 parts of modified particles, 10 parts of additives, 8.6 parts of dispersant, 3.2 parts of adhesion promoter, 6.6 parts of curing agent, 2.1 parts of leveling agent, 0.9 parts of defoaming agent, and 168 parts of deionized water.
[0058] The waterborne polyurethane emulsion is an anionic waterborne polyurethane emulsion purchased from Jining Fangyu Chemical Co., Ltd., with a solid content of 42%, a viscosity of 410 mPa·s, and a test condition of 25°C.
[0059] The preparation method of the modified functional resin comprises the following steps, calculated by mass: S1: adding 5.2 parts of ethylene glycol diacrylate, 2.2 parts of mercaptoethyl acrylate and 10.4 parts of acrylonitrile to acryloyl chloride, introducing nitrogen, adding 0.08 parts of potassium persulfate, heating to 80°C and reacting for 4.5 hours to obtain a pre-product solution; S2: adding 33.5 parts of acrylamide, 5.6 parts of dodecyl acrylate, 280 parts of deionized water and 0.19 parts of potassium persulfate to the pre-product solution obtained in S1, and heating to 85°C and reacting for 7 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding triethanolamine to adjust the pH to 7.2, and after completion, filtering and washing the product to obtain the product.
[0060] The preparation method of modified particles comprises the following steps, calculated by mass: S1: adding 3.4 parts of carbon black and 1.18 parts of zinc oxide to 80 parts of DMF solution, adding 1.55 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane and heating to 70°C, stirring for reaction for 3 hours, cooling naturally to room temperature after the reaction is completed, and washing and filtering the product to obtain mixed particles; S2: adding 2.4 parts of the mixed particles to 80 parts of DMF solution again, adding 1.24 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane for a second time. 26 parts of 3-aminopropyltriethoxysilane, and at the same time add 0.58 parts of trimesic acid and an aqueous solution containing 1.31 parts of copper nitrate (a total of 20 parts) and ultrasonically disperse for 15 minutes to obtain a mixed solution; S3: the mixed solution is added to a high-pressure reactor and heated to 110°C and kept warm for reaction for 12.5 hours; S3: after the reaction is completed, triethanolamine is added and mixed and stirred for 1 hour to adjust the pH to 7.4 to obtain the final product, the final product is centrifuged and filtered, washed with methanol and vacuum dried at 80°C for 3 times, and it is obtained after completion.
[0061] The average particle size of carbon black was 45 nm, and it was purchased from Tianjin Xinglongtai Chemical Products Technology Co., Ltd.; the average particle size of zinc oxide was 15 nm; and the average particle size of the modified particles was 687 nm.
[0062] The additives are thickener and mildew preventer, and the mass ratio of the two is 9.4:0.6.
[0063] The mildew inhibitor is zinc acetate.
[0064] The thickener is a composition of hydroxyethyl cellulose and polyvinyl alcohol 2488, and the mass ratio of the two is 4.2:1.8.
[0065] The dispersant was cetyl alcohol polyoxyethylene ether, O-5 product purchased from Haian Guoyun Chemical Co., Ltd., with a hydroxyl value of 115 mgKOH / g.
[0066] The adhesion promoter is a composition of γ-aminopropyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane, and the mass ratio of the two is 2.2:1.
[0067] The curing agent is hexamethylene diisocyanate. The leveling agent is polyethylene wax, which is a Q-18PE wax product purchased from Wuhan Xindongyi Chemical Co., Ltd.
[0068] The defoamer is silicone defoamer BYK-066N.
[0069] The second aspect of the present embodiment provides a method for preparing the coating material for the above-mentioned coated aluminum plate, which specifically includes the following steps: first, the modified particles and the modified functional resin are evenly mixed and then added to a high-speed mixer together, and then the aqueous polyurethane emulsion, deionized water and the remaining raw materials are added in sequence, the temperature is raised to 45°C, and the high-speed mixing is carried out at 400rpm for 35 minutes. Finally, the mixed material is ground and dispersed in a grinder for 5 hours. After completion, it is naturally cooled to room temperature, and the product is left to stand for 4 hours.
[0070] Example 2
[0071] Example 2 The first aspect provides a coating material for a laminated aluminum plate. The raw materials are, in parts by mass: 90 parts of aqueous polyurethane emulsion, 25.2 parts of modified functional resin, 22 parts of modified particles, 6 parts of additives, 8 parts of dispersants, 3.2 parts of adhesion promoters, 6.6 parts of curing agents, 2.1 parts of leveling agents, 0.9 parts of defoaming agents, and 168 parts of deionized water.
[0072] The waterborne polyurethane emulsion is an anionic waterborne polyurethane emulsion purchased from Jining Fangyu Chemical Co., Ltd., with a solid content of 42%, a viscosity of 410 mPa·s, and a test condition of 25°C.
[0073] The preparation method of the modified functional resin comprises the following steps, calculated by mass: S1: adding 5.2 parts of ethylene glycol diacrylate, 2.2 parts of mercaptoethyl acrylate and 10.4 parts of acrylonitrile to acryloyl chloride, introducing nitrogen, adding 0.08 parts of potassium persulfate, heating to 80°C and reacting for 4.5 hours to obtain a pre-product solution; S2: adding 33.5 parts of acrylamide, 5.6 parts of dodecyl acrylate, 280 parts of deionized water and 0.19 parts of potassium persulfate to the pre-product solution obtained in S1, and heating to 85°C and reacting for 7 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding triethanolamine to adjust the pH to 7.2, and after completion, filtering and washing the product to obtain the product.
[0074] The preparation method of modified particles comprises the following steps, calculated by mass: S1: adding 3.4 parts of carbon black and 1.18 parts of zinc oxide to 80 parts of DMF solution, adding 1.55 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane and heating to 70°C, stirring for reaction for 3 hours, cooling naturally to room temperature after the reaction is completed, and washing and filtering the product to obtain mixed particles; S2: adding 2.4 parts of the mixed particles to 80 parts of DMF solution again, adding 1.24 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane for a second time. 26 parts of 3-aminopropyltriethoxysilane, and at the same time add 0.58 parts of trimesic acid and an aqueous solution containing 1.31 parts of copper nitrate (a total of 20 parts) and ultrasonically disperse for 15 minutes to obtain a mixed solution; S3: the mixed solution is added to a high-pressure reactor and heated to 110°C and kept warm for reaction for 12.5 hours; S3: after the reaction is completed, triethanolamine is added and mixed and stirred for 1 hour to adjust the pH to 7.4 to obtain the final product, the final product is centrifuged and filtered, washed with methanol and vacuum dried at 80°C for 3 times, and it is obtained after completion.
[0075] The average particle size of carbon black was 45 nm, and it was purchased from Tianjin Xinglongtai Chemical Products Technology Co., Ltd.; the average particle size of zinc oxide was 15 nm; and the average particle size of the modified particles was 687 nm.
[0076] The additives are thickener and mildew preventer, and the mass ratio of the two is 9.4:0.6.
[0077] The mildew inhibitor is zinc acetate.
[0078] The thickener is a composition of hydroxyethyl cellulose and polyvinyl alcohol 2488, and the mass ratio of the two is 4.2:1.8.
[0079] The dispersant was cetyl alcohol polyoxyethylene ether, O-5 product purchased from Haian Guoyun Chemical Co., Ltd., with a hydroxyl value of 115 mgKOH / g.
[0080] The adhesion promoter is a composition of γ-aminopropyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane, and the mass ratio of the two is 2.2:1.
[0081] The curing agent is hexamethylene diisocyanate. The leveling agent is polyethylene wax, which is a Q-18PE wax product purchased from Wuhan Xindongyi Chemical Co., Ltd.
[0082] The defoamer is silicone defoamer BYK-066N.
[0083] The second aspect of the present embodiment provides a method for preparing the coating material for the above-mentioned coated aluminum plate, which specifically includes the following steps: first, the modified particles and the modified functional resin are evenly mixed and then added to a high-speed mixer together, and then the aqueous polyurethane emulsion, deionized water and the remaining raw materials are added in sequence, the temperature is raised to 45°C, and the high-speed mixing is carried out at 400rpm for 35 minutes. Finally, the mixed material is ground and dispersed in a grinder for 5 hours. After completion, it is naturally cooled to room temperature, and the product is left to stand for 4 hours.
[0084] Comparative Example 1
[0085] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the coating material for the coated aluminum plate, in parts by mass, the raw materials are: 95.2 parts of aqueous polyurethane emulsion, 12.5 parts of modified functional resin, 24.5 parts of modified particles, 5 parts of additives, 8.6 parts of dispersant, 3.2 parts of adhesion promoter, 6.6 parts of curing agent, 2.1 parts of leveling agent, 0.9 parts of defoaming agent, and 168 parts of deionized water.
[0086] Comparative Example 2
[0087] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the coating material for the coated aluminum plate, in parts by mass, the raw materials are: 98.6 parts of aqueous polyurethane emulsion, 27.7 parts of modified functional resin, 10.4 parts of modified particles, 10 parts of additives, 4.2 parts of dispersant, 3.2 parts of adhesion promoter, 6.6 parts of curing agent, 2.1 parts of leveling agent, 0.9 parts of defoaming agent, and 168 parts of deionized water.
[0088] Comparative Example 3
[0089] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified functional resin comprises the following steps, calculated by mass: S1: adding 2.5 parts of ethylene glycol diacrylate, 1.2 parts of mercaptoethyl acrylate and 5.4 parts of acrylonitrile to acryloyl chloride, introducing nitrogen, adding 0.05 parts of potassium persulfate, heating to 80°C and reacting for 4.5 hours to obtain a pre-product solution; S2: adding 44.5 parts of acrylamide, 6 parts of dodecyl acrylate, 280 parts of deionized water and 0.21 parts of potassium persulfate to the pre-product solution obtained in S1, and heating to 85°C and reacting for 7.5 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding triethanolamine to adjust the pH to 7.3, after completion, the product is filtered and washed to obtain the product.
[0090] Comparative Example 4
[0091] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified functional resin comprises the following steps, calculated by mass: S1: adding 5.2 parts of ethylene glycol diacrylate, 2.2 parts of mercaptoethyl acrylate and 10.4 parts of acrylonitrile to acryloyl chloride, introducing nitrogen, adding 0.08 parts of potassium persulfate, heating to 80°C and reacting for 4.5 hours to obtain a pre-product solution; S2: adding 20.8 parts of acrylamide, 9.5 parts of dodecyl acrylate, 280 parts of deionized water and 0.22 parts of potassium persulfate to the pre-product solution obtained in S1, and heating to 85°C and reacting for 7 hours after nitrogen fully replaces the reaction system gas; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding triethanolamine to adjust the pH to 7.2, and after completion, filtering and washing the product to obtain the product.
[0092] Comparative Example 5
[0093] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps, calculated by mass: S1: adding 3.4 parts of carbon black and 0.45 parts of zinc oxide to 80 parts of DMF solution, adding 1.55 parts of succinic anhydride and 0.12 parts of 3-aminopropyltriethoxysilane and heating to 70°C, stirring for reaction for 3 hours, cooling naturally to room temperature after the reaction is completed, and washing and filtering the product to obtain mixed particles; S2: adding 2.4 parts of the mixed particles to 80 parts of DMF solution again, and re-adding 2.4 parts of the mixed particles to 80 parts of DMF solution for a second time. Add 1.24 parts of succinic anhydride and 0.26 parts of 3-aminopropyltriethoxysilane, and at the same time add 0.58 parts of trimesic acid and an aqueous solution containing 1.31 parts of copper nitrate (a total of 20 parts) and ultrasonically disperse for 15 minutes to obtain a mixed solution; S3: add the mixed solution to a high-pressure reactor, heat it to 110°C, and keep it warm for 12.5 hours; S3: after the reaction is completed, add triethanolamine and mix and stir for 1 hour to adjust the pH to 7.4 to obtain the final product, centrifuge and filter the final product, wash with methanol and vacuum dry it at 80°C for 3 times, and it is obtained after completion.
[0094] The average particle size of the modified particles is 487 nm.
[0095] Comparative Example 6
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified particles comprises the following steps, calculated by mass: S1: adding 3.4 parts of carbon black and 1.18 parts of zinc oxide to 80 parts of DMF solution, adding 1.55 parts of succinic anhydride and 0.42 parts of 3-aminopropyltriethoxysilane and heating to 70°C, stirring for reaction for 3 hours, cooling naturally to room temperature after the reaction is completed, and washing and filtering the product to obtain mixed particles; S2: adding 4.5 parts of the mixed particles to 80 parts of DMF solution again, and re-adding 4.5 parts of the mixed particles to 80 parts of DMF solution for a second time. Add 1.64 parts of succinic anhydride and 0.46 parts of 3-aminopropyltriethoxysilane, and at the same time add 0.25 parts of trimesic acid and an aqueous solution containing 0.88 parts of copper nitrate (a total of 20 parts) and ultrasonically disperse for 15 minutes to obtain a mixed solution; S3: add the mixed solution to a high-pressure reactor, heat it to 110°C, and keep it warm for 12.5 hours; S3: after the reaction is completed, add triethanolamine and mix and stir for 1 hour to adjust the pH to 7.2 to obtain the final product, centrifuge and filter the final product, wash with methanol and vacuum dry it at 80°C for 3 times, and it is obtained after completion.
[0097] The average particle size of the modified particles is 802 nm.
[0098] Comparative Example 7
[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the average particle size of carbon black is 85 nm, purchased from Tianjin Xinglongtai Chemical Products Technology Co., Ltd.; the average particle size of zinc oxide is 50 nm; and the average particle size of modified particles is 947 nm.
[0100] Performance Evaluation
[0101] Antistatic property: The surface resistance of the coating materials prepared in the examples and comparative examples was tested under the following conditions: temperature 25°C, relative humidity 50%. The surface of the coating material was tested using a surface resistivity meter. The test value was the average of 10 tests and recorded in Table 1.
[0102] Waterproofness: The sessile drop method was used to test the surface water contact angle of the coating material after curing. The coating thickness was 2.5 mm, the water drop was 2.5 μL, and the test time was 20 s. The test value was the average of 10 tests and recorded in Table 1.
[0103] Mechanical properties: The tensile strength of the coating material was tested in accordance with standard GB / T 19250-2023. The average value of 10 tests was recorded in Table 1.
[0104] Aging resistance: Place the cured coating in a constant temperature and humidity box at 65°C and 75% humidity for 3 months. After 3 months, observe whether there are cracks, bubbles, yellowing or oxidation damage. If there are any, it is considered unqualified, otherwise it is qualified. 50 samples are tested in each group. The aging resistance qualified rate (%) = qualified number / 50×100%. The qualified rate results are recorded in Table 1.
[0105] Table 1 Performance test results
[0106]
[0107]
[0108] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, antistatic properties and aging resistance. This is mainly due to the combined effect of the modified functional resin and modified particles specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A coating material for a film-coated aluminum plate, characterized in that: The raw materials are as follows, by mass: 75-95 parts of waterborne polyurethane emulsion, 25-40 parts of modified functional resin, 20-30 parts of modified particles, 5-15 parts of additives, 6-12 parts of dispersants, 2-5 parts of adhesion promoters, 5-8 parts of curing agents, 1.5-3 parts of leveling agents, 0.5-1.5 parts of defoaming agents, and 140-200 parts of deionized water; The mass ratio of the aqueous polyurethane emulsion, the modified functional resin and the auxiliary agent is (8-9): (2.5-3.5): (0.6-1.4); The solid content of the aqueous polyurethane emulsion is 40-50%; The viscosity of the aqueous polyurethane emulsion is 300-500 mPa·s, and the test condition is 25° C.; The preparation method of the modified functional resin comprises the following steps: S1: adding ethylene glycol diacrylate, mercaptoethyl acrylate and acrylonitrile to an organic solvent, introducing nitrogen, adding an initiator, heating to 70-90°C for reaction for 4-5 hours to obtain a pre-product solution; S2: adding acrylamide, dodecyl acrylate, deionized water and an initiator to the pre-product solution obtained in S1, fully replacing the gas in the reaction system with nitrogen, heating to 80-90°C for reaction for 4-8 hours; S3: after the reaction is completed to obtain the product, adding acetone to wash the homopolymer, and adding an alkali agent to adjust the pH to 7-7.5, and after completion, filtering and washing the product to obtain the product; The mass ratio of ethylene glycol diacrylate, mercaptoethyl acrylate and acrylonitrile is (4-6): (2-3): (8-12); The mass ratio of acrylonitrile, acrylamide and dodecyl acrylate is (8-12):(30-40):(5-6); The preparation method of the modified particles comprises the following steps: S1: adding carbon black and zinc oxide to a DMF solution, adding succinic anhydride and a silane coupling agent, heating to 65-75°C, stirring for reaction for 2-3h, cooling naturally to room temperature after the reaction is completed, washing and filtering the product to obtain mixed particles; S2: adding the mixed particles back to the DMF solution, adding succinic anhydride and a silane coupling agent for a second time, and simultaneously adding trimesic acid and an aqueous solution containing copper nitrate for ultrasonic dispersion for 10-15min to obtain a mixed solution; S3: adding the mixed solution to a high-pressure reactor, heating to 90-110°C, and keeping the temperature for reaction for 10-15h; S3: adding triethanolamine after the reaction is completed, mixing and stirring for 0.5-1h, adjusting the pH to 7-7.5 to obtain a final product, centrifuging and filtering the final product, washing with methanol, and vacuum drying at 80-90°C for multiple cycles, and obtaining the final product after completion; In S1, the mass ratio of carbon black, zinc oxide, succinic anhydride and silane coupling agent is (3-4): (1.1-1.2): (1.4-1.8): (0.4-0.5); The average particle size of the carbon black is 40 to 60 nm; The average particle size of the zinc oxide is 10 to 25 nm; The mass ratio of trimesic acid to copper nitrate in the mixed particles is (2-2.5):(0.4-0.6):(1.1-1.5).
2. The coating material for coated aluminum plate according to claim 1, characterized in that: The mass ratio of the aqueous polyurethane emulsion, the modified particles and the dispersant is (8-9): (2.2-2.8): (0.8-1.2).
3. The coating material for coated aluminum plate according to claim 2, characterized in that: The aqueous polyurethane emulsion is an anionic aqueous polyurethane emulsion.
4. The coating material for coated aluminum plate according to claim 3, characterized in that: The silane coupling agent is at least one of 3-aminopropyltriethoxysilane, vinyltriethoxysilane and γ-aminopropyltrimethoxysilane.
5. The coating material for coated aluminum plate according to claim 4, characterized in that: The auxiliary agent at least includes a thickener and a mildew preventer; the mass ratio of the thickener to the mildew preventer is (5-10): (0.5-1.5).
6. The coating material for coated aluminum plate according to claim 5, characterized in that: The thickener is a composition of hydroxyethyl cellulose and polyvinyl alcohol; the mass ratio of the hydroxyethyl cellulose to the polyvinyl alcohol is (4-6): (1-2).
7. A method for preparing a coating material for a film-coated aluminum plate according to any one of claims 1 to 6, characterized in that: The specific steps include: First, the modified particles and modified functional resin are mixed evenly and added to a high-speed mixer. Then, water-based polyurethane emulsion, deionized water and remaining raw materials are added in sequence. The temperature is raised to 40-50°C and mixed at a high speed of 300-450rpm for 30-45min. Finally, the mixed materials are ground and dispersed in a grinder for 4-6h. After completion, they are naturally cooled to room temperature. The product is left to stand for 2-4h.
Citation Information
Patent Citations
External wall panel insulating coating and preparation method thereof
CN109233476A
Powder coating and preparation method thereof
CN112300667A